건축물 계단에서의 연돌효과 저감방안에 대한 현장실험 연구 - 김정엽(Jung-Yup Kim); 김지석(Ji-Seok Kim); 이수각(Su-Gak Lee) (설비공학 논문집, 27(9), 2015)
The winter stack effect that occurs in vertical construction passages such as the stairwell or elevator shaft of a high-rise building negatively affects living environments, energy usage, and personal safety; therefore, a mitigation of the stack effect is required to improve building conditions. Recently, circulation-type facilities that comprise the usage of air blowers and vertical ducts were proposed as part of a mechanical approach to quantitatively control the stack effect. In this study, these circulation-type facilities were installed in a building stairwell and the performance of the device was evaluated during its operation. A numerical-analysis result was obtained under the test conditions using a network-model-based, numerical-analysis method, and the result was then used for a comparison with the test result.